PENGARUH WORK FROM HOME TERHADAP KINERJA KARYAWAN DI MASA PANDEMI COVID 19 - Lilis Sulastri (AKSELERASI: Jurnal Ilmiah Nasional, 2021)
Working from home (WFH) has been implemented at PT. Sakti Mandiri Gifari Makassar in order to investigate the impact of WFH on employee performance and employee performance procedures during the influenza epidemic. The descriptive quantitative methodologies were used in this study, and a sample of 113 respondents from PT. Sakti Mandiri Gifari Makassar was selected using a random sampling methodology for the study. On the basis of the findings of the descriptive statistical test analysis, the data validity test, and the regression analysis, it can be concluded that Work from Home (WFH) has a high link with employee performance (t = 4.757) and has a statistically significant effect (p = 0.000). As a result, in this analysis, we accept Ha and reject HO, which indicates that the WFH variable (X) has a statistically significant effect on the employee performance variable (Y).